Amplifier HiFi Stereo 20 Watts / Azman Mohamed Eusoff and Rozaide Yaakup - Mohamed Eusoff, Azman; Yaakup, Rozaide (2001)
This project is called “Amplifier HiFi Stereo 20Watts'. This amplifier has been equipped with volume control, bass control, treble control and balance. The operation can be divided into four (4) different groups, they are, input signal, controlling, processing and output signal. Amplifier is used to increase an output signal from low input signal to a much greater output signal. In this amplifier, TDA2002 IC acts as an audio amplifier. It is well used with audio appliances such as Walkman or discman.